Ecodesign for Cities and Suburbs - Barnett, Jonathan; Beasley, Larry (Island Press, 2015)
In six comprehensively illustrated chapters, the authors explain ecodesign concepts, including the importance of preserving and restoring natural systems while also adapting to climate change; minimizing congestion on highways and at airports by making development more compact, and by making it easier to walk, cycle and take trains and mass transit; crafting and managing regulations to insure better placemaking and fulfill consumer preferences, while incentivizing preferred practices; creating an inviting and environmentally responsible public realm from parks to streets to forgotten spaces; and finally how to implement these ecodesign concepts.